2020
DOI: 10.1259/bjrcr.20200098
|View full text |Cite
|
Sign up to set email alerts
|

Acute Flaccid Myelitis in COVID-19

Abstract: Spinal cord imaging findings in COVID-19 are evolving with the increasing frequency of neurological symptoms among COVID-19 patients. Several mechanisms are postulatedto be the cause of central nervous system affection including direct virusneuroinvasive potential, post infectious secondary immunogenic hyperreaction, hypercoagulability, sepsis and possible vasculitis as well as systemic and metabolic complications associated with critical illness. Only a few case reports of spinal cord imaging finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 6 publications
2
66
0
12
Order By: Relevance
“…The symptoms of our rst case happened abruptly 7 days after acute symptoms of COVID-19 and were severe in nature and the patient had poor treatment outcome. These symptoms were very similar to previous cases of COVID-19 related transverse myelitis reported by Kang Zhao et al, Abdelhady et al and Alketbi et al (12)(13)(14) The abrupt onset of symptoms in these cases was similar to spinal cord infarction. Furthermore neck or back pain is another symptom of cord infarction and this symptom was declared by our patient.…”
Section: Discussionsupporting
confidence: 90%
“…The symptoms of our rst case happened abruptly 7 days after acute symptoms of COVID-19 and were severe in nature and the patient had poor treatment outcome. These symptoms were very similar to previous cases of COVID-19 related transverse myelitis reported by Kang Zhao et al, Abdelhady et al and Alketbi et al (12)(13)(14) The abrupt onset of symptoms in these cases was similar to spinal cord infarction. Furthermore neck or back pain is another symptom of cord infarction and this symptom was declared by our patient.…”
Section: Discussionsupporting
confidence: 90%
“…After review of the 242 documents, we identified 430 patients with COVID-19 diagnosed based on PCR or serologic testing who had acute neurological symptoms prompting CSF testing [ [5] , [6] , [7] , [8] , [9] , [10] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , …”
Section: Resultsmentioning
confidence: 99%
“…Complete recovery was seen in 1/18(5.6%) ( Chow et al, 2020 ), moderate improvement in 5/18 (27.7%) ( Zhou et al, 2019 ; Novi et al, 2020 ; Munz et al, 2020 ; Sarma et al, 2020 ; AlKetbi et al, 2020 ), mild improvement in 9/18(50.0%) ( Zoghi et al, 2020 ; Maideniuc et al, 2020 ; Valiuddin et al, 2020 ; Masuccio et al, 2020 ; Zachariadis et al, 2020 ; Águila-Gordo et al, 2020 ; Sotoca et al, 2020 ; Baghbanian et al, 2020 ), no improvement in 1/18(5.6%) ( Kaur et al, 2020 ) and 2 deaths (11.1%) ( Chakraborty et al, 2020 ; Abdelhady et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%